Model-based insulin-nutrition administration for glycemic control in Malaysian critical care: First pilot trial - Abu-Samah A.; Ahamad N.H.; Razak N.N.; Suhaimi F.M.; Jamaluddin U.K.; Ralib A.M.; Mat-Nor M.B.; Pretty C.G.; Dickson J.L.; Chase G. (Springer Verlag, 2023)
Biomedical engineering; Blood; Insulin; mHealth; Nutrition; Stars; User interfaces; Clinical trial; Critical care; Glycemic control; Hyperglycemia; Model based approach; Glucose